MEMÓRIA, MÍDIA E TRANSMISSÃO RELIGIOSA: ESTUDO DE CASO DA REVISTA ADVENTISTA (1906-2010) - Santos, Rodrigo Follis (2017)
This thesis discusses the transmission of the religious memory of Brazilian Adventism, focusing on the use of electronic communication (radio, television and internet). The theoretical background was based on the aspects of memory and religious transmission, especially its tension between continuity and rupture within the modernizing process. For this, the sociology of religious memory built by Halbwachs was chosen. This combination allowed us to analyze how the theology of the group studied articulates past events to justify beliefs and habits of the present. The delimitation of the corpus was found in the Revista Adventista, between 1906 and 2010, which was used as a mirror of a larger reality, the carrier of the transitions and continuities of the memory discourse. The work is structured through a content analysis together with a qualitative approach on the discourses. The logic of the chapters begins with the historiographical construction of the thought and development of brazilian and world adventism to later include the copies of the publication that deal with aspects of the use of the founding memory of the group, as well as all the apparitions of the terms "radio" "television" and "internet." As part of the results, we note how the Seventh-day Adventist Church's (SDA) conception of producing a rationalistic preaching based on reading and searching for the "correct" interpretation of the biblical text brings some important characteristics to this movement, shaping your missiology and worldview. The use of the founding past was seen through reports about the pioneers, notably Ellen G. White. We have also seen that there are re-significances of some constitutive bases of the identity of the movement, which defy the denomination in its attempt to remain faithful to its founding message. The research revealed an ambiguous relationship between brazilian adventism and the media, which is associated with the tensions arising from modernity. There is a tension experienced by the memory of the brazilian movement regarding the use and refusal of the communicational instruments. This relationship is mainly due to a utilitarian vision, which sees in the message delivered, and not in the medium itself, dangers to be avoided by the movement.